Nutrients and heavy metals in the straits of Johor - Yusof, Mufidatul Iman (2016)
In this study, marine water quality together with land use effect on Johor Straits along Kampung Pasir Putih was investigated. Changes in land use and increased discharge of domestic, agricultural and industrial waste into the coastal water have severely affected the water condition and threatened fishing and green mussel aquaculture activity. According to fisherman there are no more fish caught in the vicinity and only crabs and mussels survive. Sampling was conducted on 26th April 2015, 27th September 2015, 15th October 2015, 1st November 2015 and 23rd November 2015. Six sampling stations were identified for marine water quality analysis based on in-situ and laboratory analysis. Dissolved oxygen (DO) concentration was between 0.43 to 6.71 mg/L. The nitrogen concentrations studied were between 0.01 to 0.22 mg/L for NO3 -, 0.02 to 0.33 mg/L for NH3-N, and 0.02 to 0.31 mg/L for TN. The phosphorus concentrations were between 0.02 to 0.31 mg/L for PO4 3- and 0.17 to 0.89 mg/L for TP. Heavy metals concentration in marine water along Kampung Pasir Putih (in mg/L) were between 0.08 to 0.33 for Ni, 0.01 to 0.09 for Zn, 0.04 to 0.19 for Cd, and 0.21 to 1.39 for Pb. Based on the selected parameters conducted, Kampung Pasir Putih is classified as Class 3 according to Malaysia Marine Water Quality Standard (MMWQS).